Utiliser Twitter pour soutenir l’engagement cognitif et socio-affectif des primo-entrants à l’université - Thierry Soubrié (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Dropping out of the university, especially in the first year of bachelor’s degrees has become a national concern. Since 2007, various actions for supporting the students have been implemented in French universities within a longitudinal national programme aiming at increasing academic achievement in first cycle degrees whether before entering university, during the degree course, or even when students seek to enter the labour market. However, little actions has been taken in order to promote educational innovation despite the fact that, according to Tinto, there is a strong link between educational innovation and “heightened forms of engagement and, in turn, to student persistence ” (2006, p. 5). We examine the use of Twitter in a class in general linguistics in order to analyse changes in the relationship with students and to enhance their cognitive, social and emotional engagement. Based on analyses of the contents of the Tweets exchanged between students during the semester, and their answers to a questionnaire at the end of the course, we aim to understand to what the extent this objective was achieved. After reviewing the results, we will suggest improvements in order to replicate this experiment.